Agent-mediated electronic commerce : designing trading strategies and mechanisms for electronic markets : AMEC/TADA 2015, Istanbul, Turkey, May 4, 2015, and AMEC/TADA 2016, New York, NY, USA, July 10, 2016, Revised selected papers /: designing trading strategies and mechanisms for electronic markets : AMEC/TADA 2015, Istanbul, Turkey, May 4, 2015, and AMEC/TADA 2016, New York, NY, USA, July 10, 2016, Revised selected papers. (2017) - Unknown
No abstract available